Effect of the poly l-lactic acid coating on the corrosion of Magnesium in Hank’s solution - Atikah Wan Nafi,; Amalina Afifi,; Nor Ishida Zainal Abidin,; Noor Hidayah Abdul Aziz,; Katayoon Kalantari, (Penerbit Universiti Kebangsaan Malaysia, 2018)
To control the corrosion rate, the Magnesium (Mg) was coated with poly (l-lactic acid) (PLLA) using electrospinning technique. The effectiveness of the PLLA coating on the high purity Magnesium (HP Mg) and alloy AZ91 were tested in Hank’s solution immersion test. The corrosion behaviour of Mg coated PLLA was studied through hydrogen evolution, weight loss and scanning electron microscope (SEM) before, during and after samples were immersed. The solution was maintained at pH 7 by bubbling CO2 gas. The results showed that surface treatment on Mg by coating with PLLA had reduced the rate of corrosion during the immersion test. The PLLA coating was also characterized and the coating adhesion was evaluated.